Efektifitas Teknik Relaksasi Napas dan Imajinasi Terbimbing terhadap Penurunan Nyeri pada Pasien Pasca Operasi di Ruang Bedah - Epi Rustiawati; Yeni Binteriawati; Aminah Aminah (Faletehan Health Journal, 2022)
Postoperative patients experience nociceptive pain due to wound incision. The uncontrolled pain impacts on the decrease of patients’ participation in care, the patients’ dissatisfaction, and the increase of length of stay. One of efforts in reducing the pain non-pharmacologically is by breathing relaxation technique and guided imagination. The purpose of this study was to determine the effectiveness of breathing relaxation technique and guided imagination on pain reduction of postoperative patients. This study used an experimental time series design and consecutive sampling technique. The sample size was 90 people consisting of 30 respondents in the control group, 30 respondents received breathing relaxation technique and 30 respondents got guided imagination treatment. The data analysis used Fiedman test and Wilcoxon Post Hoc test. The results of Fiedman test (p value 0.0001) showed differences in pain reduction among the control group, the breathing relaxation technique group and the guided imagination group in the 1st, 2nd and 3rd days (p<0.05). Meanwhile, the Wilcoxon test results (p value 0.302) showed no significant difference in the decrease of pain intensity between the breathing relaxation technique group and the guided imagination group (p> 0.05). The combination of breathing relaxation technique, guided imagination and pharmacological techniques can be applied as an effort of providing nursing services in pain reduction among postoperative patients.